Corononema vulgare sp. n. and Hofmaenneria coralis sp. n. (Nematoda, Monhysterida) from coral reefs off the coast of Vietnam - Phuong, Nguyen Thi Xuan; Long, Phan Ke; Thanh, Tran Thi Viet; V.g., Gagarin; V.o., Mokievsky; Tu, Nguyen Dinh (Zootaxa, 2023)
Two new nematode species of the order Monhysterida, found in coral reefs on the coast of Vietnam, are described and illustrated. Corononema vulgare sp. n. morphology is similar to C. thai Nicholas & Stewart, 1995 but differs from it by the shorter outer labial setae, shorter tail in males, and a different shape of the guiding lateral bodies in the spicular apparatus of males. Hofmaenneria coralis sp. n. morphology is close to H. niddensis Gerlach & Meyl, 1957 and H. optata Alekseev, 1983. The new species differs from the first species by having thinner body, a shorter and less slender tail, and shorter spicules. The new species differs from H. optata in having a longer body, shorter pharynx, shorter tail, and longer outer labial setae.